How image‐guided core needle biopsies altered the treatment of breast disease: Challenges accepted and opportunities taken. Issue 6 (9th May 2020) - Lester, Susan C.
Abstract: The technique of combining stereotactic targeting of breast lesions with an automated spring‐loaded needle biopsy gun reported in 1990 by Steve Parker and colleagues not only ushered in the era of diagnosis almost exclusively by image guided core needle biopsy, but also profoundly changed the practice of pathologists, radiologists, surgeons, and medical oncologists and had major effects on the treatment of women with breast cancer. In this special issue of The Breast Journal celebrating 25 years of publication, it is of value to reflect back on these changes, some expected and some unanticipated, which have occurred over the past three decades and to consider the reasons why core needle biopsies should be considered a milestone in breast pathology.